Bone rattle - Cameron, Marc (Cameron, Marc. Arliss Cutter novel., 2021)
Pulled from their duties to keep track of sequestered jurors in a high-profile trial involving a massive drug conspiracy, Arliss Cutter and deputy Lola Teariki realize that they are dealing with something much bigger, and darker, than a simple drug trial when the prosecuting attorney is murdered.